Atypical MRI Findings in Cerebral Adrenoleukodystrophy: a Case Report - Koray Koç; Arzu Canan; Pınar Koç; Kamil Karaali; Özgür Duman; Utku Şenol (Acta Clinica Croatica, 2021)
Adrenoleukodystrophy is a rare X-linked hereditary disease that results in accumulation of very-long-chain fatty acids in all body tissues, thus causing demyelination of the white matter. Magnetic resonance imaging (MRI) is a reliable radiological modality to demonstrate the extension of brain lesions and severity of the disease. In the classic form, the parieto-occipital white matter is affected. Besides, atypical MRI findings such as primary frontal lobe involvement are rarely described. We report a case of adrenoleukodystrophy presenting with rare MRI findings such as bilateral symmetric frontal lobe white matter changes suggesting anterior predominance.